Prospective observational study of conjunctival scarring after phacoemulsification. (11th May 2016) - Gozawa, Makoto; Takamura, Yoshihiro; Miyake, Seiji; Yokota, Satoshi; Sakashita, Masanori; Arimura, Shogo; Takihara, Yuji; Inatani, Masaru
Abstract: Purpose: To examine whether anterior segment‐optical coherence tomography (AS‐OCT) can detect conjunctival scarring after transscleral phacoemulsification and whether temporal transscleral phacoemulsification causes scarring in the superior conjunctiva. Methods: Transscleral phacoemulsification was performed in the superior conjunctiva (superior incision group) or the temporal conjunctiva (temporal incision group). Anterior segment‐optical coherence tomography (AS‐OCT) images of the superior conjunctiva were obtained before and after surgery. We quantified the thickness of the conjunctiva and preservation rates of the borderlines among the subconjunctival layers. The relationship between the AS‐OCT images and histology was evaluated in rabbit eyes with phacoemulsification. Results: Each group comprised 25 patients. At ≤1 month after surgery, the superior conjunctiva was significantly thicker in the superior incision group than the temporal incision group (1 day, 7 days, and 1 month after surgery; p   <   0.0001, p   <   0.0001, and p   <   0.001 respectively); however, there were no significant differences between the two groups at ≥2 months. The borderline of the conjunctival stroma/Tenon's capsule and the borderline of the Tenon's capsule/sclera were preserved significantly better in the temporal incision group after surgery (p   <   0.0001). The cell densities in the conjunctiva of the rabbit temporal incision group were unchanged after surgery, whereas the rabbit superior incision group had significantly more neutrophils (p   =   0.0001) and myofibroblasts (p   <   0.0001) in the superior conjunctiva than the temporal incision group. Conclusions: Anterior segment‐optical coherence tomography (AS‐OCT) images can detect conjunctival scarring after transscleral phacoemulsification. The layer structures in the superior conjunctiva are unaffected by temporal transscleral incision.